2001
DOI: 10.1177/154193120104501420
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Head, Forearm and Back Support on Myoelectric Activity, Performance and Subjective Comfort during a VDT Task

Abstract: VDT work consists of static muscle activity in the arms, neck, shoulders and back to keep the head and hands in a mostly fixed working position. The aim of this study was to investigate alternative VDT workstation configurations that may reduce the muscle force of these static contractions by providing support to the head/neck, arm and back regions of the body. Effects of an inclined chair back with headrest and a chair mounted split keyboard (CMSK) were investigated. For a typing task, combining a CMSK with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, very little has been published regarding the impact of supine or significantly reclined postures on the performance of computer-related tasks. One paper by Monroe (Monroe et al, 2001) compared the use of a split keyboard and a standard (straight) keyboard in both a reclined and an upright posture as they related to typing performance and comfort. Monroe found that there was no significant difference in typing performance with the straight keyboard when moving from an upright to a reclined posture.…”
Section: Introductionmentioning
confidence: 99%
“…However, very little has been published regarding the impact of supine or significantly reclined postures on the performance of computer-related tasks. One paper by Monroe (Monroe et al, 2001) compared the use of a split keyboard and a standard (straight) keyboard in both a reclined and an upright posture as they related to typing performance and comfort. Monroe found that there was no significant difference in typing performance with the straight keyboard when moving from an upright to a reclined posture.…”
Section: Introductionmentioning
confidence: 99%